2009
DOI: 10.1210/jc.2008-2541
|View full text |Cite
|
Sign up to set email alerts
|

Greater Adipose Tissue Infiltration in Skeletal Muscle among Older Men of African Ancestry

Abstract: Our analyses suggest that despite lower total adiposity, skeletal muscle fat infiltration is greater among African than among Caucasian ancestry men and is associated with T2D in both ethnic groups. Additional studies are needed to determine the mechanisms contributing to ethnic differences in skeletal muscle adiposity and to define the metabolic and health implications of this fat depot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 56 publications
0
62
2
Order By: Relevance
“…This finding is in line with other previous data, in particular, a study using mouse models, which showed that LPS injections can lead to changes in muscle quality (31). Ectopic skeletal muscle adiposity is greater among African ancestry individuals than Caucasians (3236) and has been shown to be an important risk factor for type 2 diabetes (37,38). Whether LBP may partly explain ethnic/racial differences in skeletal muscle adiposity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with other previous data, in particular, a study using mouse models, which showed that LPS injections can lead to changes in muscle quality (31). Ectopic skeletal muscle adiposity is greater among African ancestry individuals than Caucasians (3236) and has been shown to be an important risk factor for type 2 diabetes (37,38). Whether LBP may partly explain ethnic/racial differences in skeletal muscle adiposity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…storage at sites not normally associated with fat deposition. In skeletal muscles, elevated adipose deposition is observed at both inter-and intra-muscular sites (Miljkovic et al 2009;Schwenzer et al 2009). The reported effects of age on hepatic adiposity are mixed; an increase in hepatic adiposity (Frith et al 2009;Li et al 2009), no change (Bedogni et al 2006;Tiikkainen et al 2002) and negative correlations (Bedogni et al 2005;Zhou et al 2007) have been observed with age.…”
Section: Ageing Associated Changes In Adipose Tissue Distributionmentioning
confidence: 99%
“…Muscle quality measurements allow for an enhanced analysis of muscle tissue through assessment of the amount of contractile versus non-contractile tissue within the muscle (Fukumoto et al 2011), and are made largely using advanced and expensive technology, such as computed tomography (CT) and magnetic resonance imaging (MRI) (Goodpaster 2001; Katsiaras et al 2005; Miljkovic et al 2009; Tracy et al 1999). MRI and CT technologies have commonly been used to quantify muscle cross-sectional area (mCSA) and, more recently, to evaluate intramuscular fat and connective tissue, as an estimate of muscle quality.…”
Section: Introductionmentioning
confidence: 99%